Advances in mechanism and regulation of PANoptosis: Prospects in disease treatment - Zhu, Peng; Ke, Zhuo-Ran; Chen, Jing-Xian; Li, Shi-Jin; Ma, Tian-Liang; Fan, Xiao-Lei (Frontiers in Immunology, 2023)
PANoptosis, a new research hotspot at the moment, is a cell death pattern in which pyroptosis, apoptosis, and necroptosis all occur in the same cell population. In essence, PANoptosis is a highly coordinated and dynamically balanced programmed inflammatory cell death pathway that combines the main features of pyroptosis, apoptosis, and necroptosis. Many variables, such as infection, injury, or self-defect, may be involved in the occurrence of PANoptosis, with the assembly and activation of the PANoptosome being the most critical. PANoptosis has been linked to the development of multiple systemic diseases in the human body, including infectious diseases, cancer, neurodegenerative diseases, and inflammatory diseases. Therefore, it is necessary to clarify the process of occurrence, the regulatory mechanism of PANoptosis, and its relation to diseases. In this paper, we summarized the differences and relations between PANoptosis and the three types of programmed cell death, and emphatically expounded molecular mechanism and regulatory patterns of PANoptosis, with the expectation of facilitating the application of PANoptosis regulation in disease treatment.